INFLUENCE OF PERCEPTION OF EASE, SERVICE FEATURES AND TRUST ON THE CUSTOMERS SATISFACTION LEVEL THE BNI DigiCS MACHINE USERS : Case Study at PT Bank Negara Indonesia KC Wonosobo - Wahyuningrum, Ike Maharani; Fatullah, Rahmat; Umam, Muhammad Khatibul; Wahyuningtyas, Yunita Fitri (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This study aims to determine the effect of perceived convenience, service features and trust affecting individually and simultaneously on the level of customer satisfaction of users of the BNI Digital Customer Service or BNI DigiCS machine at Bank BNI Wonosobo branch office. This research was conducted using quantitative methods, data processing was carried out using the SPSS version 26 application. The population is customers and prospective customers of Bank BNI KC Wonosobo. This research sampling technique uses non probability sampling techniques. This study used a sample of 96 people. This study uses multiple linear regression analysis methods as a data analysis method. The results of this study indicate that based on the test of the coefficient of determination (R2), it can be seen that the value of the coefficient of determination (R2) is 0.345, which means that 34.5% of the level of customer satisfaction using BNI DigiCS machine services at Bank BNI KC Wonosobo (Y) is jointly influenced by perceived convenience (X1), service features (X2), and trust (X3), while the remaining 65.5% is influenced by other factors not included in this study.